Effects of self-directed learning readiness, resilience, and competencies on learning motivation of postgraduate students in Malaysian research universities - Mohammad Din, Izumy Dihafiny (2015)
The purpose of this study was to examine the relationship between self-directed learning readiness and learning motivation with the mediating effects of resilience and competencies among postgraduate students in Malaysia. There were five objectives in this study: (i) to identify the relationship between selfdirected learning readiness and resilience, (ii) to examine the relationship between self-directed learning readiness and learning motivation, (iii) to study the relationship between self-directed learning readiness and competencies, (iv) to assess the mediating effect of resilience in the relationship between selfdirected learning readiness and learning motivation, and (v) to investigate the mediating effect of competencies in the relationship between self-directed learning readiness and learning motivation. A total of 600 questionnaires were distributed to postgraduate students from four Research Universities (RUs) in Malaysia namely Universiti Malaya, Universiti Putra Malaysia, Universiti Kebangsaan Malaysia, and Universiti Teknologi Malaysia. Respondents were selected using stratified sampling and simple random sampling. After the data collection completed, data was analysed through a few steps which include data screening, descriptive analysis, multivariate assumption test, reliability and validity test, and lastly hypothesis testing. To test the hypotheses of this study, simple regression, multiple regression, and mediation regression analysis were used. Results showed that from five main hypotheses, three hypotheses were supported and the other two hypotheses were not supported. It can be concluded from the findings that self-directed learning readiness has a significant and positive relationship between learning motivation, resilience, and competencies. However, there is no mediation of resilience and competencies were found in the relationship between self-directed learning readiness and learning motivation.